2014
DOI: 10.1021/am500464n
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3D-Nanonet Hollow Structured Co3O4 for High Capacity Supercapacitor

Abstract: A 3D-nanonet structured cobalt-basic-carbonate precursor has been obtained by a facile, low cost and eco-friendly route under ambient temperature and pressure. After calcination in air, the as-prepared precursor was converted to a 3D-nanonet hollow structured Co3O4 with its original frame structure almost preserved. Encouragingly, by alternating experimental parameters (Table S1 in the Supporting Information ), such as concentration of the starting reagents and calcination temperature, we got the optimized con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
172
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(185 citation statements)
references
References 55 publications
6
172
0
1
Order By: Relevance
“…In addition, the C 1s peak can be observed at 285.6 eV because of the CANACo formation [57]. The N-doped carbon was also evidently proved by C 1s XPS spectra that the CAN formation which causes the adsorption of water on the catalyst surface was observed for the O1s XPS spectra of N-doped carbon of Co 3 O 4 ; this can be attributed to the formation of physical and chemical adsorption, O adsorbates on the surface of defects [25,59].…”
Section: Catalyst Characterizationmentioning
confidence: 86%
“…In addition, the C 1s peak can be observed at 285.6 eV because of the CANACo formation [57]. The N-doped carbon was also evidently proved by C 1s XPS spectra that the CAN formation which causes the adsorption of water on the catalyst surface was observed for the O1s XPS spectra of N-doped carbon of Co 3 O 4 ; this can be attributed to the formation of physical and chemical adsorption, O adsorbates on the surface of defects [25,59].…”
Section: Catalyst Characterizationmentioning
confidence: 86%
“…The electrochemical properties of the as-prepared films were investigated by galvanostatic charge-discharge (GCD, CHI 1140A) and cyclic voltammetry (CV, CHI 1140A) tests in a NaOH aqueous solution of different concentration. A three electrode cell was employed in the electrochemical tests with the working electrode being the as-prepared nickel hydroxide film, 6 while the counter and the reference electrode being a graphite rod and a saturated calomel electrode respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the realization of the high-efficient energy storage and conversion has become one of the greatest scientific and engineering challenges in the 21 st century [1][2][3][4][5][6]. Supercapacitors or electrochemical capacitors have attracted significant interest as energy-storage devices not only due to its long cycle life and high power density compared with dielectric capacitors and rechargeable batteries but also due to its broad applications in portable electronic devices, hybrid electric vehicles and medical devices [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…And it is demonstrated that porous hierarchical structures can bring about excellent performances in electrochemical energy storage systems with their high specific surface area. Driven by this, hollow/hierarchical Co 3 O 4 architectures have gained great interest and been successfully synthesized by various methods [19][20][21][22][23][24][25]. Among these methods, chemical templating (sometimes called sacrificial templating) process can provide a straightforward and powerful route for the controllable synthesis of hollow structures [26][27][28].…”
Section: Introductionmentioning
confidence: 99%